2020
DOI: 10.1007/s40122-020-00211-2
|View full text |Cite
|
Sign up to set email alerts
|

Basivertebral Nerve Ablation for the Treatment of Vertebrogenic Pain

Abstract: Chronic low back pain affects a significant portion of patients worldwide and is a major contributor to patient disability; however, it is a difficult problem to diagnose and treat. The prevailing model of chronic low back pain has presumed to follow a discogenic model, but recent studies have shown a vertebrogenic model that involves the basivertebral nerve (BVN). Radiofrequency ablation of the BVN has emerged as a possible nonsurgical therapy for vertebrogenic low back pain. The objective of this manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 68 publications
0
22
0
1
Order By: Relevance
“…There is no radicular expression, lower extremity weakness, nor sensory deficits and the neural tension sign and pain tends to be worse with spinal flexion, sitting, standing and with general physical activity, in contrast to extension. 17 , 26 , 28 , 29 To provide additional insight on vertebrogenic pain symptomatology responsive to BVNA, aggregated data from over 320 clinical trial reported by Relievant Medsystems, patients revealed that 70% of patients indicated their pain location as midline on body diagrams and less than 6% reported pain below the mid-gluteal region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is no radicular expression, lower extremity weakness, nor sensory deficits and the neural tension sign and pain tends to be worse with spinal flexion, sitting, standing and with general physical activity, in contrast to extension. 17 , 26 , 28 , 29 To provide additional insight on vertebrogenic pain symptomatology responsive to BVNA, aggregated data from over 320 clinical trial reported by Relievant Medsystems, patients revealed that 70% of patients indicated their pain location as midline on body diagrams and less than 6% reported pain below the mid-gluteal region.…”
Section: Discussionmentioning
confidence: 99%
“…Per the foundational studies discussed at length moving forward in this manuscript, BVN RFA may be successfully utilized in patients with axial chronic low back pain of vertebral etiology of at least 6-months duration, who have failed conservative treatment for at least 6-months, have radiological evidence of MCs type 1 or type 2 on MRI between the L3-S1 spinal segments while also fulfilling a number of other criteria discussed at length later, namely the absence of radicular symptoms, no history of previous lumbar surgery, and no osteoporosis, etc. 1 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations